Almost Impossible Leadership: Understanding the Crisis in Polish Academia - Czekierda, Piotr (Stan Rzeczy, 2024)
Dominant leadership models, derived from business or politics, fail to address the unique nature of academia. This article proposes the integral leadership model, tailored to the specific challenges of universities, particularly in the Polish context. Drawing on data from 36 in-depth interviews and polarity management theory (Johnson, Koestenbaum), the article argues that inherent tensions (polarities) at every level of the academic system are a key factor in understanding leadership complexities. Unlike problems requiring a single solution (A OR B), polarities necessitate managing seemingly opposing elements (A AND B) for long-term effectiveness. This framework sheds light on the challenges faced by academic leadership in Poland across three dimensions: individual, organisational, and moral. Individual challenges include a lack of aspiring leaders and inadequate role models. Organisational challenges stem from prioritising stability over change and individual over team. Moral challenges arise from a lack of clarity about leadership goals and values, resulting in conflicts between excellence and relations (inclusion). The article emphasises the growing need for integral leadership that acknowledges and manages these particular polarities.